ANALISIS KEKUATAN IMPAK KOMPOSIT HYBRID SERAT LONTAR DAN SERAT GELAS UNTUK APLIKASI HELM KENDARAAN BERMOTOR - Andre Juanda Baru; Jefri S. Bale; Yeremias M. Pell (Universitas Nusa Cendana, 2022)
The fiber content of lontar fruit can be utilized in a non-metal composite substitute for a more expensive metal composite. Currently, non-metallic materials are widely used as substitutes for metal materials because they have various advantages, namely being lighter in weight, easier to shape, and cheaper. One of these non-metallic materials is fiberglass. The purpose of this study was to determine the effect of alkali treatment on the impact properties of polyester fiber reinforced palm fiber and glass fiber composites, the effect of concentrations of 5%, 10%, and 15% Alkali (NaOH) on the impact properties, and treatment time 0, 2, 4, and 6 hours on Impact properties of polyester composites reinforced with palm fiber and glass fibers. 20% of the test specimens were made according to the ASTMD256-04 standard and tested with an impact tester. The results of the impact test showed that composites with hybrid fibers (palm fiber and glass fiber) as well as composites with palm fiber which were treated with alkali tended to have greater impact properties than those not treated with alkali. Fiber-reinforced composites treated with 15% alkali had the highest average toughness, while the lowest impact toughness was composites with fiber reinforcement treated with 5% alkali. The length of time of treatment had an effect on the impact toughness of the composites.